Different This Time? The Prospects of CCS in the Netherlands in the 2020s - Akerboom, Sanne; Waldmann, Svenja; Mukherjee, Agneev; Agaton, Casper; Sanders, Mark; Kramer, Gert Jan (Frontiers in Energy Research, 2021)
Carbon capture and storage (CCS) has been recognized as an important means to mitigate global climate change, but apart from several pilots, it has not yet been successfully implemented on a large-scale. In the Netherlands, CCS has long been the subject of debate, as three unsuccessful projects in the past demonstrate. However, CCS has been accorded an important place in the current Dutch climate policies, being expected to contribute up to 7 Mt of CO2 reduction. This is reflected in a fresh crop of CCS project plans. For the most, these plans have a long way to go from the drawing board to actual operations due to the technical, economic, legal and societal challenges ahead. In this article we review the status and possibilities of CCS in the Netherlands from an interdisciplinary perspective, basing our analysis on existing literature in the different disciplines. First, a brief overview of the technology options for carbon capture and storage or utilization is given, followed by a detailed analysis of the governmental support for CCS, given the vital role that fit-for-purpose legal frameworks and policy instruments will play in CCS deployment. Since the investment uncertainties are another major factor inhibiting CCS roll out, this article then delves into a real options economic analysis of a CCS project in three different business cases. Finally, as societal acceptance has proved to be a major barrier for CCS worldwide, the conditions that enhance public acceptance of CCS are examined. Our work shows that while CCS is technically a straightforward proposition, its deployment has historically been stymied by the lack of a compelling and stable socio-technical narrative. The main argument in favor of CCS today is that it offers a transition measure for rapidly and massively reducing CO2 emissions beyond what could be accomplished by alternative methods like electrification and renewable fuels. The introduction of new financial instruments, increased government support and an improvement in social engagement appear to have enhanced the prospects of CCS, but empirical evidence based on actual project deployment is necessary to judge the progress that has been made in fact.